Development of a Service Excellence Model for Customer Satisfaction in Schools - Pamuji Raharjo; Ribut Wahyu Eriyanti; Hari Sunaryo (Electronic Journal of Education, Social Economics and Technology, 2025)
In the current era of globalization, customer satisfaction is one of the key benchmarks for assessing the quality of services in various sectors, including education. The development of a Service Excellence model aimed at enhancing customer satisfaction in schools is crucial to achieving educational quality. This model not only focuses on the service aspect but also encompasses improvements in teaching quality and parental involvement in the educational process. Therefore, the implementation of this model is expected to create a better learning environment and encourage collaboration among all stakeholders to achieve optimal educational goals. The application of this model also provides schools with the opportunity to adapt to the needs and expectations of students and parents, resulting in a more relevant and fulfilling educational experience. Consequently, collaboration between schools, students, and parents becomes a vital factor in creating an innovative and responsive learning atmosphere. By integrating technology into education and supporting efficient communication, schools can build a more engaging and suitable learning experience for students. Innovation in curriculum and teaching methods can also enhance student creativity, preparing them to face future challenges with better skills and a deeper understanding of a constantly changing world. Ongoing evaluation should not be overlooked, as it allows schools to adjust their strategies and ensure that every student receives the support they need to reach their full potential.